2019
DOI: 10.4103/jisp.jisp_44_19
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Enterococcus faecalis in subgingival biofilms of healthy, gingivitis, and chronic periodontitis subjects

Abstract: Background:Enterococcus faecalis is a Gram-positive, facultative anaerobic coccus that can survive under harsh conditions. Studies have shown a positive relationship between biofilm formation and gelE gene expression in E. faecalis. The production of gelatinase (MMP 2) has been detected in 50% of E. faecalis isolates from endodontic and periodontal infections, which suggests its role in the pathogenesis of apical and marginal periodontitis. Although E. faecalis is not considered a periodontopathogen, this spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 8 publications
3
8
0
1
Order By: Relevance
“…4,22,[24][25][26]33 In contrast, oral enterococci have commonly been detected in lower prevalence when microbial cultivation is used. 4,11,27,39 In accordance with our data, Rams et al 39 were able to isolate around 6% of enterococci strains from subgingival plaque of patients with periodontitis, whereas other investigators reported detection rates around 7% in oral rinses from patients with oral diseases. 11,40 Higher frequencies, however, were found in the subgingival biofilm of an Indian population (26.8%), 27 as well as in oral rinses from a healthy Brazilian cohort (16.6%), 15 and saliva (21.8%) from healthy North Americans.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…4,22,[24][25][26]33 In contrast, oral enterococci have commonly been detected in lower prevalence when microbial cultivation is used. 4,11,27,39 In accordance with our data, Rams et al 39 were able to isolate around 6% of enterococci strains from subgingival plaque of patients with periodontitis, whereas other investigators reported detection rates around 7% in oral rinses from patients with oral diseases. 11,40 Higher frequencies, however, were found in the subgingival biofilm of an Indian population (26.8%), 27 as well as in oral rinses from a healthy Brazilian cohort (16.6%), 15 and saliva (21.8%) from healthy North Americans.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, variation in enterococci detection rates may occur as a result of various factors other than detection techniques. Regardless of the methodology used, our findings agree with the majority of the investigations, [24][25][26][27]31 showing higher isolation/detection rates of oral enterococci, mainly E. faecalis, in individuals with periodontal diseases (gingivitis, 7.8% and periodontitis, 9.8%) than PH (2.2%) (Fig. 3).…”
Section: Discussionsupporting
confidence: 90%
“…puede estar relacionada con infecciones periodontales aunque no es una bacteria de gran relevancia en estos cuadros (27) , por sus características puede colonizar la región aunque la presencia del factor Gel E (gelatina extracelular) una enzima encargada de hidrolizar y degradar colágeno, hemoglobina y fibrinógeno, puede generar una destrucción del periodonto, produciendo una mayor severidad de la periodontitis (28) .…”
Section: E Faecalisunclassified
“…[ 2 ] It can get incorporated into the oral cavity by food contaminants and also by nosocomial infections. E. faecalis has also been related to various oral diseases, such as caries, endodontic infections, chronic periodontitis (41.7%)[ 3 ] and peri-implantitis. It is a persistent organism that plays a major role in the etiology of secondary periradicular lesions after the root canal treatment.…”
Section: Introductionmentioning
confidence: 99%